Energy system contribution during 200- to 1500-m running in highly trained athletes - Spencer, M. R.; Gastin, P. B. (Medicine & Science in Sports & Exercise, 2001)
PURPOSE: The purpose of the present study was to profile the aerobic and anaerobic energy system contribution during high-speed treadmill exercise that simulated 200-, 400-, 800-, and 1500-m track running events. METHODS: Twenty highly trained athletes (Australian National Standard) participated in the study, specializing in either the 200-m (N = 3), 400-m (N = 6), 800-m (N = 5), or 1500-m (N = 6) event (mean VO2 peak [mL x kg(-1)-min(-1)] +/- SD = 56+/-2, 59+/-1, 67+/-1, and 72+/-2, respectively). The relative aerobic and anaerobic energy system contribution was calculated using the accumulated oxygen deficit (AOD) method. RESULTS: The relative contribution of the aerobic energy system to the 200-, 400-, 800-, and 1500-m events was 29+/-4, 43+/-1, 66+/-2, and 84+/-1%+/-SD, respectively. The size of the AOD increased with event duration during the 200-, 400-, and 800-m events (30.4+/-2.3, 41.3+/-1.0, and 48.1+/-4.5 mL x kg(-1), respectively), but no further increase was seen in the 1500-m event (47.1+/-3.8 mL x kg(-1)). The crossover to predominantly aerobic energy system supply occurred between 15 and 30 s for the 400-, 800-, and 1500-m events. CONCLUSIONS: These results suggest that the relative contribution of the aerobic energy system during track running events is considerable and greater than traditionally thought.